Social protection and food security - Hidrobo, Melissa; Hoddinott, John F.; Kumar, Neha; Olivier, Meghan (International Food Policy Research Institute, 2014)
Halving global hunger has been one of the preeminent Millennium Development Goals (MDGs) over the last 15 years (United Nations, 2000) and its elimination is a key component of post-MDG objectives (HLPEP, 2013). Raising incomes is essential for this goal to be met. There are many ways in which this can be accomplished - increasing productivity of smallholders, increasing levels of education, reducing barriers to entry to high return activities, to name a few. This paper examines one way of raising incomes of poor households, social protection interventions, and the contribution these make to improving household food security and the reduction of hunger.